Perceptions of staff on collegiality and accountability in promoting quality assurance at Helderberg College - Appollis, Jilian Rosemary (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Curriculum Studies))--University of Stellenbosch, 2009.